TEKNIK PENGGUNAAN MEDIA SOSIAL “FACEBOOK DAN INSTAGRAM” DALAM MEMBANGUN BRAND AWARENESS PT. WISATA ANUGERAH ABADI - Ahmad Fadhilah (Jurnal Visi Komunikasi, 2020)
Companies in the current era use social media as a medium for the formation of Brand Awareness, specifically social media Facebook and Instagram. Wina Tour is an effort that is engaged in the field of Tour & Travel services that use social media Facebook and Instagram to make Brand Awareness as Agnet Travel. The purpose of this research is to study the results of using Facebook and Instagram social media in the formation of Wina Tour Brand Awareness.This research refers to the theory about the technique put forward by Uchjana Effendy The technique is essentially planning and management to achieve a goal. But achieving that goal, the technique does not function as a road map that only shows direction, but must be able to show how the operational point is.The method used in this research is qualitative descriptive through in-depth interviews with Vienna Tour social media managers and Vienna Tour customers using Facebook and Instagram.The results of this study indicate that the utilization of Facebook and Instagram by Wina Tour in the formation of the desired image has been successful, where through published content, Vienna Tour customers Facebook and Instagram users have the perception that on Vienna Tour they get information about traveling. But there are still things that need to be maximized by Wina Tour to be able to achieve the goal of forming its image to the fullest.